TEACHING AIDS AND PLAYING TOOLS AS LEARNING MEDIA FOR KINDERGARTEN AND PRE-SCHOOL STUDENTS - ajes, editor (Academic Journal of Educational Sciences, 2024)
Teaching aids and playground equipment are important for PAUD and TK students. This is important because PAUD and kindergarten age children are still in the stage of growth and development, Physical growth will affect physical, physicological, cognitive, personality and social development. This development will affect the maturity of students. With props and playground equipment, students can develop their imagination. By playing, they can dovarious things with the tools. There is a critical and creative thinking process in constructing props and playground equipment for cognitive, motor and psychomotor development. In addition, they feel happy and joyful.